2019
DOI: 10.1016/j.dental.2019.08.098
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the interface failure of yttria partially stabilised zirconia - porcelain dental prostheses through microscale residual stress and phase quantification

Abstract: Highlights  Residual stress and phase analysis at the microscale at interface and coping edge  X-ray diffraction and Raman spectroscopy show comparable results  Cross validation using ring-core focused ion beam and digital image correlation  Monoclinic and highly stressed regions identified close to interface  Phase transformation volumetric expansion is the origin of porcelain failure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 83 publications
1
13
1
7
Order By: Relevance
“…This validation has recently been provided in the literature, which shows nominally identical stress profiles in the two orientations being considered in this study (A. Lunt et al, 2019). Within an equibiaxial system, Mohr's circle for stress collapses to a single point, such that there are no shear stresses within this plane (Timoshenko, 1925).…”
Section: Theory and Modellingsupporting
confidence: 52%
See 3 more Smart Citations
“…This validation has recently been provided in the literature, which shows nominally identical stress profiles in the two orientations being considered in this study (A. Lunt et al, 2019). Within an equibiaxial system, Mohr's circle for stress collapses to a single point, such that there are no shear stresses within this plane (Timoshenko, 1925).…”
Section: Theory and Modellingsupporting
confidence: 52%
“…In order to assess the validity of the proposed model, the residual stress and YPSZ phase distribution obtained in this study will be compared on those previously determined experimentally (A. Lunt et al, 2019). This analysis was performed on a representative incisal prosthesis which was produced from Wieland Dental Zenotec Zr bridge.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the interface between the two ceramics is one of the weakest aspects, and delamination and chipping of the veneering ceramic is the main failure mode of bilayer zirconia restorations [11][12][13][14]. A recent study evaluated the zirconia-veneer interface and reported new insights that explain the high chipping rates observed [15]. Successive generations of zirconia have been developed to solve the chipping problem of the first-generation zirconia and to improve its translucency [11,14].…”
Section: Introductionmentioning
confidence: 99%